2003
DOI: 10.1016/s0195-668x(03)00258-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of cardiac troponin T in the long-term risk stratification of patients undergoing percutaneous coronary intervention

Abstract: Our study confirms the long-term prognostic value of pre-procedural TnT elevation in patients undergoing PCI, and demonstrates the superior predictive ability of a post-procedural increase in TnT 5x normal for long-term adverse events. Whether the prognostic significance of smaller post-procedural TnT elevations extends beyond the intermediate-term awaits further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 31 publications
1
57
0
2
Order By: Relevance
“…[5][6][7]9 A postprocedure increase in cTnI concentration of Ͼ5-fold baseline levels is an independent predictor of a composite of death, MI, and revascularization at 1 year (hazard ratio, 2.39; 95% CI, 1.09 to 5.26). 7 Gadolinium late enhancement with cardiac magnetic resonance has demonstrated that procedural cTnI release is due to MI both downstream of the stented lesion and adjacent to the implanted stent. 3,25 Microembolization of plaque debris and side-branch occlusion have been proposed as the most likely mechanisms of cTnI release.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7]9 A postprocedure increase in cTnI concentration of Ͼ5-fold baseline levels is an independent predictor of a composite of death, MI, and revascularization at 1 year (hazard ratio, 2.39; 95% CI, 1.09 to 5.26). 7 Gadolinium late enhancement with cardiac magnetic resonance has demonstrated that procedural cTnI release is due to MI both downstream of the stented lesion and adjacent to the implanted stent. 3,25 Microembolization of plaque debris and side-branch occlusion have been proposed as the most likely mechanisms of cTnI release.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] A number of studies have demonstrated that procedure-related troponin release is associated with subsequent cardiovascular events. [5][6][7][8][9] …”
mentioning
confidence: 99%
“…13 It has also been demonstrated that elevation of troponin T is relatively common among patients with stable CAD undergoing PCI and is an independent prognostic indicator of ischemic complications. 4,5 Prasad et al found that an isolated minor elevation in troponin T after PCI without a rise in CK-MB following PCI provided long-term prognostic information regarding mortality and MI. 6 Several reports have shown that an increase in cardiac troponin T can be found in a proportion of patients after PCI ranging from less than 10% to almost 50%.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 It has also been reported that elevation of troponin T is relatively common among patients with stable coronary artery disease undergoing PCI and is an independent prognostic indicator of ischemic complications. 4,5 However, there were few studies about comprehensive risk factor analysis of troponin T elevation in patients with stable CAD after drug-eluting stent (DES) implantation. Therefore, we designed this clinical study to chronic inflammation; (7) dysfunction of hematological and immunological system; or (8) carcinoma or a condition treated with immunosuppressive agents.…”
Section: Introductionmentioning
confidence: 99%
“…cTn release after PCI ranges in incidence from 14% to 48% (77)(78)(79)(80)(81)(82). This wide variation is caused by the assay and corresponding cutoff concentrations used, as well as the underlying indication for the revascularization procedure (e.g., acute vs elective) and the type of procedure performed.…”
Section: Biomarkers After Pcimentioning
confidence: 99%